Third dose of anti-SARS-CoV-2 inactivated vaccine for patients with RA: Focusing on immunogenicity and effects of RA drugs - Zhao, Ting; Wang, Bo; Shen, Jiayan; Wei, Yuanyuan; Zhu, Youyang; Tian, Xiaofang; Wen, Guangfen; Xu, Bonan; Fu, Chenyang; Xie, Zhaohu; Xi, Yujiang; Li, Zhenmin; et al. (Frontiers in Medicine, 2022)
Objectives: To evaluate the immunogenicity of the third dose of inactivated SARS-CoV-2 vaccine in rheumatoid arthritis (RA) patients and explore the effect of RA drugs on vaccine immunogenicity. Methods: We recruited RA patients (n=222) and healthy controls (HC, n=177) who had been injected with a third dose of inactivated SARS-CoV-2 vaccine, and their neutralizing antibody (NAb) titer levels were assessed. Results: RA patients and HC were age- and gender-matched, and the mean interval between 3rd vaccination and sampling was comparable. The NAb titers were significantly lower in RA patients after the third immunization compared with HC. Furthermore, comparison of NAb titers between RA treatment subgroups and HC showed that the combined treatment of traditional Chinese medicine (TCM) and DMARDs produced a higher response compared to DMARD monotherapy. Compared with the HC, patients in the csDMARDs group exhibited no significant change in NAb, while those in the bsDMARDs, JAK inhibitor, and prednisone groups, the NAb titers were significantly lower. Spearman correlation analysis revealed that NAb responses to SARS-CoV-2 in HC did differ significantly according to the interval between 3rd vaccination and sampling, but this finding was not observed in RA patients. In addition, NAb titers were not significantly correlated with RA-related laboratory indicators, including RF-IgA, RF-IgG, RF-IgM, anti-CCP antibody; C-RP; ESR; NEUT% and LYMPH%. Conclusion: Serum antibody responses to the third dose of vaccine in RA patients were weaker than HC. A combined treatment of TCM and DMARDs produced a higher response, emphasizing that TCM could improve vaccine responses.